Tarsal fixation of Fascia lata in Frontalis Sling Ptosis Surgery - Moin, Muhammad (Pakistan Journal of Ophthalmology, 2006)
Purpose: To evaluate the results of tarsal fixation of fascia lata in frontalis sling ptosis surgery Design: Interventional case series. Material and Methods: Retrospective review of all cases of ptosis surgery performed between January 2000 and June 2005 in one of the units of Institute of Ophthalmology, Mayo Hospital, Lahore. Patients with levator function of less than 4 mm in the worst affected eye were included. All patients undergoing frontalis sling with materials other than fascia lata and all children under 5 years were excluded. Bilateral frontalis sling was performed only in cases having ptosis on both sides while unilateral surgery was done in other cases. Results: Out of 108 cases of ptosis frontalis sling for the correction of poor function ptosis was performed on 57 eyelids of 41 patients. Out of 41 cases of poor function ptosis 16 cases (39 %) were bilateral and 25 cases were unilateral (12 right and 13 left). Thirty six patients had simple congenital ptosis with poor levator function, 3 patients had jaw winking unilateral ptosis and 2 cases had blepharophimosis syndrome. All patients had severe ptosis with average preoperative margin to reflex distance (MRD) of – 0.95 ± 1.33 mm. All eyelid in unilateral cases and worst eye in bilateral cases had poor levator function averaging 3.8 ± 1.35 mm in average levator function in better eyelid of bilateral cases was 4.25 ± 2.29 mm. Amblyopia was seen in 8 patients and strabismus was seen in 6 patients. Average post-operative MRD with brow up was 3.55 ± 0.73 mm and with brow down was 2.15 mm at 3 months after surgery. Unilateral cases had results comparable to bilateral cases although it took the patients a few months before learning to keep the 2 sides at equal height. All patients had a well formed lid crease and were happy with the postoperative lid height. No patient had lagophthalmos of more than 2 mm. Two cases undergoing unilateral surgery had slippage of the sling which needed to be readjusted at the end of the first week. Five eyes had mild exposure keratopathy initially which was resolved with lubricants over 1 month. Mild nasal peaking was seen in 4 eyelids which was apparent only on the limit of brow action and was cosmetically acceptable to the patient. Conclusion: Tarsal fixation of fascia lata sling produces a deep lid crease with reliable correction of poor function ptosis.